Perancangan Sistem Task Management Pada CV. Balinet Intermedia Menggunakan MVC (Model-View-Controller) - Sulistyadewi, Ni Putu; Sastrawangsa, Gde; Wulandari, Riza (Technomedia Journal, 2023)
The use of innovation from a technical standpoint is a step toward starting a business. The task management process, including task recording, assignment, and reporting, has not been integrated at CV. Balinet Intermedia, making it difficult to monitor the performance of the many company divisions. The goal of this research is to develop a task management system design document for CV. Balinet Intermedia using Model-View-Controller (MVC) approach to define the three key components of a system that alter data, show information to users, and operate the system. Data gathering methodologies include observation, interviews, and literature reviews. The system design makes use of Use Case Diagrams, Context Diagrams, and Entity Relationship Diagrams (ERD), while the model make use of Class Diagram Models and controller designs make use of Data Flow Diagrams. Additionally, this task management system has tools for managing user information, clients, teams, tasks, notes, login logs, task submission, task verification, and task report printing. The average score obtained from the design suitability evaluation questionnaire with the user was 89 points. The study's conclusions serve as a documentation that is in line with user needs in order to act as a guide for system implementation in the future. Keywords: CV. Balinet Intermedia, Task Management, Model View Controller, MVC